(untitled) (Comparative Professional Pedagogy, 2024)
The article is devoted to the comparative analysis of pharmacists’ professional training in universities in Ukraine and the United Kingdom. The criteria for comparison are identified and substantiated. The current legislative and regulatory framework in the field of pharmaceutical education in both the UK and Ukraine is analysed. It is noted that despite progress in reforming pharmaceutical education, Ukraine lags behind global trends, particularly those in the UK, where standards and programs are updated in line with market demands. It is established that the key difference in the management of pharmaceutical education systems in Ukraine and the UK lies in the level of decentralization. An analysis of pharmacy training programs at leading universities in Ukraine and the UK is presented. A comparative study of the structural, content-based, and organizational-pedagogical principles of the professional training for master’s degree pharmacists in two countries is provided. It is determined that a significant difference between the educational programs for master’s degree lies in the level of specialization and student mobility. The article highlights certain positive aspects of the organization of the educational process in pharmacy training under the MPharm program in the UK universities, including interdisciplinary training, integrated programs, the absence of a general education cycle, and a particular emphasis on analytical and research-oriented modules. It is established that one of the key elements of master’s pharmacy programs (MPharm) in the UK universities is the focus on practical training, particularly clinical and research components. The article notes that the research work of students studying for master’s degree in Pharmacy has an applied dimension in the UK. In contrast, the aim of qualification theses of master’s degree in Pharmacy at Ukrainian higher education institutions is theoretical problem study. In conclusion, the harmonization of theoretical training with modern practical methods and adaptation to international standards are identified as key directions for improving pharmaceutical education in Ukraine.